Sensitization of Cancer Cells for Chemo/Immuno/Radio-therapy - Bonavida, Benjamin (Cancer Drug Discovery and Development,, 2008)
Cancer chemotherapy can be traced back to the 1940's and since then the world has witnessed the discovery and the important application of several new drugs. The successes of combination chemotherapy suggested that all cancers can be treated provided that the correct combination of drugs at the correct doses and correct intervals are established. However, with time, tumor cells develop mechanisms of resistance to apoptosis and no longer respond to the majority of cytotoxic therapies. Sensitization of Cancer Cells for Chemo/Immuno/Radio-therapy, edited by Benjamin Bonavida, reviews novel approaches developed to reverse tumor cell resistance to chemo/immuno/radio-therapy and the use of various sensitizing agents in combination with various cytotoxics. Such sensitizing agents target gene products that regulate resistance and therefore identify novel targets for drug development. This book also introduces several of the current approaches that have been developed by established investigators in the field that are aimed at overcoming resistance. This book is the first that compiles studies on tumor cell sensitization and is useful for students, scientists, clinicians and pharmaceutical companies.